1999
DOI: 10.1248/bpb.22.275
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and Diuretic Effect after Administration of Retarded Capsules of Bumetanide in Human Subjects.

Abstract: Retarded capsules containing 1 mg bumetanide (BN) were prepared and their in vivo absorption and diuretic effect after oral administration in human subjects were studied. For comparison, commercially available tablets of BN (rapid effect) were administered orally. The mean value of the area under the plasma concentration time curve (AUC) after administration of retarded capsules was about one half that of the tablets. The mean maximum plasma concentration (Cmax) and the mean maximum urinary excretion rate of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…However, in the case of the bumetanide retarded capsules a clockwise hysteresis was evident in the relationship between urinary excretion rate and urine flow rate. In this case the urine flow rate maximum was achieved before the plasma C max or maximum of urinary excretion in the case of bumetanide [20]. Similar results were obtained with furosemide (another loop diuretic) for which minimal counter-clockwise hysteresis was observed for plain tablets (Furix®) while controlled release formulations (Furix Retard® and Lasix Retard®) exhibited clear clockwise hysteresis when the diuretic effect versus furosemide excretion rate were correlated [38].…”
Section: Input Rate: Pharmaceutical Formulation Effects and The Direcmentioning
confidence: 67%
See 3 more Smart Citations
“…However, in the case of the bumetanide retarded capsules a clockwise hysteresis was evident in the relationship between urinary excretion rate and urine flow rate. In this case the urine flow rate maximum was achieved before the plasma C max or maximum of urinary excretion in the case of bumetanide [20]. Similar results were obtained with furosemide (another loop diuretic) for which minimal counter-clockwise hysteresis was observed for plain tablets (Furix®) while controlled release formulations (Furix Retard® and Lasix Retard®) exhibited clear clockwise hysteresis when the diuretic effect versus furosemide excretion rate were correlated [38].…”
Section: Input Rate: Pharmaceutical Formulation Effects and The Direcmentioning
confidence: 67%
“…For instance, bumetanide as a tablet exhibited counter-clockwise hysteresis because a time lag between plasma concentration and diuretic effect is evident since the drug acts directly in the renal tubule or because of variations in absorption rate from the GI tract. However, in the case of the retarded capsules a clockwise hysteresis was present because the maximum urine flow rate was achieved before the plasma C max or before the maximum of urinary excretion [20]. Thus, it can be clearly observed that the pharmaceutical formulation may change the pharmacodynamics of a drug.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations